Comparative Spectroscopic Investigation of Tm3+:Tellurite Glasses for 2-μm Lasing Applications - Huseyin Cankaya (Applied Sciences, 2018)
We performed a comparative spectroscopic analysis on three novel Tm3+:tellurite-based glasses with the following compositions Tm2O3:TeO2-ZnO (TeZnTm), Tm2O3:TeO2-Nb2O5 (TeNbTm), and Tm3+:TeO2-K2O-Nb2O5 (TeNbKTm), primarily for 2-μm laser applications. Tellurite glasses were prepared at different doping concentrations in order to investigate the effect of Tm3+ ion concentration as well as host composition on the stimulated emission cross sections and the luminescence quantum efficiencies. By performing Judd–Ofelt analysis, we determined the average radiative lifetimes of the 3H4 level to be 2.55 ± 0.07 ms, 2.76 ± 0.03 ms and 2.57 ± 0.20 ms for the TeZnTm, TeNbTm and TeNbKTm samples, respectively. We clearly observed the effect of the cross-relaxation, which becomes significant at higher Tm2O3 concentrations, leading to the quenching of 1460-nm emission and enhancement of 1860-nm emission. Furthermore, with increasing Tm2O3 concentrations, we observed a decrease in the fluorescence lifetimes as a result of the onset of non-radiative decay. For the 3H4 level, the highest obtained quantum efficiency was 32% for the samples with the lowest Tm2O3 ion concentration. For the 1860-nm emission band, the average emission cross section was determined to measure around 6.33 ± 0.34 × 10−21 cm2, revealing the potential of thulium-doped tellurite gain media for 2-μm laser applications in bulk and fiber configurations.